Geologi Situs Menapo Ujung Tanjung II, Kabupaten Muaro Jambi, Provinsi Jambi - Fadhlan Intan (Tumotowa, 2020)
Menapo Unjung Tanjung II holds a cultural heritage, from the Hindu-Buddhist period which has not received the attention of environmental researchers. This is the main problem that covers general geological conditions. Therefore, the purpose of this research is to map surface geology in general as an effort to present geological information, while the aim is to find out the geomorphological, stratigraphic, geological structure, and hydrological aspects. The research method begins with a literature review, survey, and interpretation of field data. Environmental observations provide information about the landscape including the terrain morphology unit. Trellis-patterned, rectangular river, old mature river, and periodic/permanent river. The constituent rocks are alluvial, and the Kasai Formation. Geological structure in the form of anticline and syncline. The hydrology consists of surface water and groundwater. Research in Menapo Ujung Tanjung II has succeeded in finding the structure of bricks, which are thought to function as waterways. This assumption cannot be justified scientifically.